Advances in the treatment of Hodgkin lymphoma: Current and future approaches - Ullah, Fauzia; Dima, Danai; Omar, Najiullah; Ogbue, Olisaemeka; Ahmed, Sairah (Frontiers in Oncology, 2023)
Hodgkin lymphoma (HL) is a rare type of lymphoma with unique histologic, immunophenotypic, and clinical features. It represents approximately one-tenth of all lymphomas in the United States and consists of two subtypes: classical Hodgkin’s lymphoma (cHL) accounts for majority of all HL cases, and nodular lymphocyte predominant Hodgkin lymphoma, representing approximately 5% of Hodgkin lymphoma cases. From this point, we will be focusing on cHL in this review. In general, it is considered a highly curable disease with first-line chemotherapy with or without the addition of radiotherapy. However, there are patients with disease that relapses or fails to respond to frontline regimens and the standard treatment modality for chemosensitive cHL is high dose chemotherapy followed by autologous hematopoietic stem cell transplant (AHSCT). In recent years, targeted immunotherapy has revolutionized the treatment of cHL while many novel agents are being explored in addition to chimeric antigen receptor (CAR) T-cell therapy which is also being investigated as a potential treatment option.